1998
DOI: 10.1175/1520-0485(1998)028<0890:ohtstb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

On Haney-Type Surface Thermal Boundary Conditions for Ocean Circulation Models

Abstract: Haney-type surface thermal boundary conditions linearly connect net downward surface heat flux Q to air-sea temperature difference (gradient-type condition) T 1 or to climate/synoptic sea temperature difference (re-storing-type condition) T 2 by a coupling coefficient. In this study, the authors used the global reanalyzed data (6-h resolution) of Q, surface air temperature T A , and sea surface temperature T O from the National Centers for Environmental Prediction during 1 October 1994-31 December 1995 to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Recent studies (Chu et al, 1998) show that the Haney type sea surface boundary condition (Haney, 1971) is not valid for regional seas. For the YES modeling, it is necessary to use all the fluxes (Chu et al 2001).…”
Section: Surface Fluxesmentioning
confidence: 99%
“…Recent studies (Chu et al, 1998) show that the Haney type sea surface boundary condition (Haney, 1971) is not valid for regional seas. For the YES modeling, it is necessary to use all the fluxes (Chu et al 2001).…”
Section: Surface Fluxesmentioning
confidence: 99%
“…The restoring timescale used in present OGCMs is typically about 30 days (Semtner and Chervin 1992;Stammer et al 1996;Marotzke and Willebrand 1991). However, analyses of the observed data revealed that sensitivity of the surface heat flux to variations of SST must be much weaker than presumed in the above values, which implies that must be much longer (Seager et al 1995;Barnier 1998;Chu et al 1998). For example, Barnier (1998) and Frankigonoul et al (1998) suggested that the restoring timescale must be at least twice as long.…”
Section: Introductionmentioning
confidence: 95%
“…Based on observations available at the time, Haney computed an average "coupling coefficient", κ, with a value of 30-45 W m -2 K -1 . Subsequent work by (Chu et al, 1998) suggests a value of 65-70 W m -2 K -1 , whereas (Frankignoul et al, 1998) suggest a value of 20 W m -2 K -1 . (Frankignoul and Kestenare, 2002) further quantified the oceanic feedback to the anomalous surface heat flux by explicitly Earth Syst.…”
Section: Fast Ocean Feedbacks: Ocean Mixed-layer Feedbacks and Ocean mentioning
confidence: 99%